Migration In The Early ’90s: Italy Coping With Albanian Illegal Emigration - Goxha, Jeta (European Scientific Journal, ESJ, 2016)
This article aims to study the role that Italy played in confronting the migratory flows in the early 90s, with a separate analysis of the Albanian case. The Italian diplomacy policies regarding the problems caused by the confrontation of the illegal immigration phenomenon will be analyzed. This research intends to provide an overview of the political and social relations between the two countries. The problem is analyzed through a bibliographic search, treating the issues in a historical and political framework. The scientific contributions on the issue under consideration are mainly the Italian legislation, archival resources taken from the Ministry of Foreign Affairs archives, reports and strategies drawn up by the Italian government, in order to avoid social and economic problems. The study method used is qualitative. This author’s interest relates to the conviction that Italy has played an important role in confronting the Albanian emigrants even though most of the time it appears without a concrete plan and at the same time contradictory. While writing this paper we will review all factors and consequences that were derived in this phenomenon.